2006
DOI: 10.1002/glia.20385
|View full text |Cite
|
Sign up to set email alerts
|

Multiple roles of Id4 in developmental myelination: Predicted outcomes and unexpected findings

Abstract: Myelination in the central nervous system is a complex process requiring the integration of oligodendrocyte progenitor differentiation and the coordinate expression of myelin genes. This study addresses the role of the helix-loop-helix protein Id4 in these two events. Overexpression of Id4 in oligodendrocyte progenitors prevents differentiation and consequently decreases the endogenous expression of all myelin genes. Conversely, progenitors lacking Id4 display precocious differentiation both in vitro and in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 42 publications
4
77
0
Order By: Relevance
“…Of the NAB-regulated genes selected by these criteria ( (33)(34)(35)(36). Schwann cells express all members of the Id family, but Id2 and Id4 levels decline during the course of myelination and are expressed at relatively low levels in mature nerve (26,37,38).…”
Section: Resultsmentioning
confidence: 99%
“…Of the NAB-regulated genes selected by these criteria ( (33)(34)(35)(36). Schwann cells express all members of the Id family, but Id2 and Id4 levels decline during the course of myelination and are expressed at relatively low levels in mature nerve (26,37,38).…”
Section: Resultsmentioning
confidence: 99%
“…He also showed that overexpression of Id4 prolongs OPC proliferation and inhibits differentiation in the presence of PDGF and TH. Toru then collaborated with Fred Sablitzky at Nottingham University to show that neural stem cells isolated from the brains of Id4-deficient mouse embryos produce oligodendrocytes prematurely in culture (Marin-Husstege et al 2006). Taken together, these findings suggest that Id4 is another component of the timer and that its progressive decrease helps control when OPCs stop dividing and differentiate.…”
Section: Some Protein Components Of the Intracellular Timermentioning
confidence: 95%
“…Furthermore, it has been shown that only Id2, and not the other members of the family, Id1 and Id3, is able to abrogate the antiproliferative effects of tumor suppressor proteins of the retinoblastoma family allowing cell-cycle progression by physically interactions with them, (Lasorella et al, 2000). Finally it is known that Id4 has an essential role in the maturation of oligodendrocytes during development, thus progenitors lacking Id4 precociously maturate (Marin-Husstege et al, 2006). In summary Id factors can work as important regulators of different biological processes and they are commonly associated to maintenance of undifferentiated state and the mitotic activity of cells, being often downregulated when cells differentiate (Lyden et al, 1999, Shimizu-Nishikawa et al, 1999Ruzinova andBenezra, 2003, Sikder et al, 2003;Iavarone and Lasorella, 2006).…”
Section: Arrows) (F)mentioning
confidence: 99%